Kesesuaian Lahan untuk Kacang Tanah (Arachis hypogaea L.) pada Zona Agroekologi-II.5 Kawasan Desa Ohoinol Kei Kecil Timur, Kabupaten Maluku Tenggara - Sibualamo, M. Gentha Yudha Sandy; Risamasu, Robby G; Ufie, Conradus; Siregar, Adelina (JURNAL PERTANIAN KEPULAUAN, 2025)
This study aims to inventory land resources and management practices of groundnut smallholder farms in the Ohoinol agricultural area. assess land suitability for groundnut in ZAE II.5. to create a land suitability map for groundnut based on predictions of relative production potential. The method used was survey method, analytical approach, free survey observation distance by conducting identification (boring) and making complete soil profiles and current land use in the sample area determined in 20 land units. The observation results found three types of soil, namely Rensina (Calsiudols), Litosol (Udorthents), and Cambisol (Eustrudepts), which were carried out on community gardens. Groundnut planting activities take place in the eastern season (summer) twice and the western season (rainy season) once. The length of the growth period (LGP) is about 240 days, compared to the peanut growth cycle of 90-140 days. the LGP has no impact on the peanut growth age of 90-140 (average 115 days) and a decrease in production; in other words, the LGP is optimal, namely 80-100% of the subsistence level production achievement of 1,305 Kg dry beans/ha (VS Class = S1). Assessment of groundnut suitability (rooting depth ± 30 cm) based on soil conditions in land units RL015 and RL215 (42 ha in total) is mostly very suitable and has no effect on reducing subsistence level production